2015
DOI: 10.1111/jai.12777
|View full text |Cite
|
Sign up to set email alerts
|

Fish by-catch in shrimp beam trawls in the northern South China Sea

Abstract: Summary The by‐catch of shrimp beam trawl fisheries in the northern South China Sea were estimated during the 2005–2006 and 2012–2013 fishing seasons. A total of 98 hauls from three important shrimp fishing grounds were used in the analyses. A total of 119 by‐catch species were captured, compared with only 15 target species. The ratio of by‐catch to shrimp ranged from 1.01 to 13.90. The dominant standard length (SL) range of fish by‐catch was 51–100 mm. The percentage of juveniles in the total catch of some fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Falling nets are a type of fishing gear that appeared and developed rapidly in the northern South China Sea in the early 1990s [9]. Falling-net fishing mainly aims to catch cephalopods and phototactic fishes.…”
Section: Introductionmentioning
confidence: 99%
“…Falling nets are a type of fishing gear that appeared and developed rapidly in the northern South China Sea in the early 1990s [9]. Falling-net fishing mainly aims to catch cephalopods and phototactic fishes.…”
Section: Introductionmentioning
confidence: 99%
“…It contributes to the highest proportion of total fishing production. But like most trawl fisheries around the world, trawl fishery in the South China Sea is also characterized by high by-catch problems due to its poor selective properties [2][3][4][5]. The Beibu Gulf has long held its esteemed status as one of the South China Sea's pivotal fishing grounds, boasting an abundance of groundfish and even setting records for the highest catch rates in bottom trawling operations.…”
Section: Introductionmentioning
confidence: 99%
“…However, over the past decade, a concerning shift has unfolded, revealing a tale of overexploitation and the rampant depletion of fishery resources within the Beibu Gulf. The once-harmonious balance has been disrupted as fishing intensity among fishermen has surged beyond optimal thresholds, triggering an alarming decline in the region's marine biodiversity [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Due to small mesh sizes used, a serious bycatch problem was induced in shrimp trawl fisheries of the SCS ( Yang et al, 2015 ; Yang et al, 2017 ). It was reported that undersized fish and juvenile shrimp constituted the majority of the bycatch species.…”
Section: Introductionmentioning
confidence: 99%